PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS AUTOPLAY MEDIA STUDIO 8.5 PADA SUBPOKOK MATERI KEPOLARAN SENYAWA DAN BENTUK MOLEKUL UNTUK KELAS X SMA/MA - Pretiwi Febriani; Betty Holiwarni; Elva Yasmi Amran (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2019)
The development of interactive learning media based on Autoplay Media Studio 8.5 is aimed to get valid interactive learning from the terms of content substance, display (visual comunication), instructional design and courseware utilization. The research method was used four-D models which consist of four stages, those are define, design, develop and desseminate. The research is up to the development stage. The data collected technique used validation sheet, questionnaire responses of students and teacher. The result showed an average score of content substance aspects, display (visual comunication) aspects, instructional design aspect and courseware utilization aspects was 91,4%. Learning media also fulfill the practical criteria based on the responses of students and teacher with a score 95,5% and 77,5%. The conclusion show the learning media based on Autoplay Media Studio 8.5 valid and can be use in learning process.